Governance of Labor Standards in Australian and German Garment Supply Chains: The Impact of Rana Plaza. (May 2019) - Schuessler, Elke; Frenkel, Stephen J.; Wright, Chris F.
This article analyzes the impact of the 2013 Rana Plaza building collapse on garment lead firms' labor standards policies in the light of new governance approaches, particularly the pathbreaking Accord on Fire and Building Safety in Bangladesh. Based on a sample of 20 Australian and German garment firms, the authors find that firms with low prior baseline standards revised their supply chain and sourcing policies and signed the Accord. Firms with medium and high baseline standards responded variously, from making no changes to revising their policies and signing the Accord. Firm response variation can be explained by stakeholder pressure occurring in different national industrial and institutional contexts following the Rana Plaza incident, which served as a focusing event. Results suggest the wider applicability of the focusing event framework for industrial relations scholarship and highlight some of the mechanisms driving changes in industrial relations institutions.